2011
DOI: 10.5372/1905-7415.0504.063
|View full text |Cite
|
Sign up to set email alerts
|

Original article. Intravenous sedation for gastrointestinal endoscopy in very elderly patients of Thailand

Abstract: Background: The use of sedation for gastrointestinal endoscopy (GIE) procedures in elderly patients has been established as a safe and effective technique. However, it is still uncertain whether the situation is valid for Asians.Objective: Evaluate the outcome of intravenous sedation (IVS) for GIE procedures in very elderly patients (>86 years old) in Thailand and compare the clinical efficacy of IVS between very elderly and those younger (<86 years old)Methods: We undertook a retrospective review of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 12 publications
0
16
2
1
Order By: Relevance
“…We usually use propofol, midazolam and fentanyl for endoscopic procedures including small bowel enteroscopy. A low dose of midazolam, combined with low dose fentanyl and propofol, was safe and effective, and did not prolong recovery time even in elderly patients [10,11,16,17] . In GA, short-acting muscle relaxants (atracurium and cisatracurium) and short-acting inhalation agents (isoflurane, sevoflurane and desflurane) are commonly used for short procedures [18] .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We usually use propofol, midazolam and fentanyl for endoscopic procedures including small bowel enteroscopy. A low dose of midazolam, combined with low dose fentanyl and propofol, was safe and effective, and did not prolong recovery time even in elderly patients [10,11,16,17] . In GA, short-acting muscle relaxants (atracurium and cisatracurium) and short-acting inhalation agents (isoflurane, sevoflurane and desflurane) are commonly used for short procedures [18] .…”
Section: Discussionmentioning
confidence: 90%
“…However, it is tempting to speculate that these patients in particular may benefit from the GA technique with less experienced endoscopists. Moreover, cardiopulmonary and other diseases which are more frequent in older patients have been regarded as the major risk factors for complications associated with endoscopy or sedation [9][10][11] . Old age as an important risk factor for endoscopy, but is not an indication for providing GA more frequently for enteroscopy at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…Considering these changes, ERCP and EUS procedures play an important role in the delivery of gastrointestinal healthcare. The proportion of these patients is increasing, and a high number of geriatric patients undergoing gastrointestinal endoscopies (GIE) have been observed 13. Although concerns remain regarding the safety and potential benefits of endoscopies, previous studies have shown that ERCP and EUS procedures can be safe and well tolerated, even in very old patients 47.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, more profound falls in blood pressure occur in a hypovolemic patient. Propofol has also been proven to reduce postprocedural hypoxemic events, which may be of significance in critically ill elderly patients [20,21] and sick pediatric patients [22,23] . Prevention of this complication is to take a relevant medical and drug history before the procedure with particular detail required regarding current antihypertensives, antianginal and antiarrhythmic therapy and the use of systemic corticosteroids.…”
Section: Complicationsmentioning
confidence: 99%